Effect of Current Ratio and Debt to Equity Ratio on Return on Assets (ROA) in food and beverage sub-sector companies for the period 2015-2021 - NadiaUlfah; HasanurArifin; Sugiharto; SetioUtomo (Magister Administrasi Bisnis ULM, 2024)
Abstract: This study aims to determine and examine the effect of Current Ratio (X1) and Debt To Equity Ratio (DER) (X2) on Return On Assets (Y) in food and beverage sub-sector companies for the 2015-2021 period. This study uses a quantitative approach and with an explanatory type. The object of this research is the Annual Financial Report of the Food and Beverage Sub-Sector Company which consists of PT. Akasha Wira Internasional Tbk, PT. Tiga Pilar Sejahtera Tbk, PT. Tri Banyan Tirta Tbk, PT. Campina Ice Cream Industry Tbk, PT. Nippon Indosari Tbk. The data used in this study is secondary data, namely the published financial statements of the Food and Beverage Sub- Sector Companies for the 2015-2021 Period. The population used in this study is the entire Annual Financial Statements of Food and Beverage Sub-Sector Companies, while the sample used is the Annual Financial Statements of 35 research periods of 7 years multiplied by 5 research objects. This research uses purposive sampling technique. The data analysis technique used is Descriptive Statistical Analysis, Classical Assumption Test, Multiple Linear Regression Analysis, and Hypothesis Testing. Results Based on research using the t test or partially on the variable Current Ratio (CR) to Return on Assets (ROA) has no significant effect. The Debt-to-Equity Ratio (DER) partially has no significant effect on Return on Assets (ROA). And the results of the simultaneous test (f test) it is known that the Current Ratio (CR) (X1) and Debt on Equity Ratio (DER) (X2) simultaneously have no significant effect on Return On Assets (ROA) is large the effect is only 3% the remaining 97%. influenced by other variables not examined in this study